“Iconoclasm” in the early years of Soviet power (1918–1921) - Rogozny, Pavel G. (Вестник Свято-Филаретовского института)
The article is devoted to the struggle against icons, which began literally in the first months after the Bolsheviks came to power. The Bolsheviks themselves called their policy “iconoclasm”. According to the “instructions” adopted in August 1918, icons and any other “religious images” should be removed from public places. However, the new authorities faced open disobedience to their orders, and it turned out to be simply impossible to remove all the icons that hung in schools, shops, hospitals, factories, etc. The outbreak of the Civil War also complicated the implementation of the final decision. On this basis, there were a number of bloody clashes with peasants unwilling to remove icons. The icon in Orthodoxy and especially in “national Orthodoxy” was revered as the greatest shrine, and many peasants were ready to look at any violence against it as an insult to the community. Even after the end of the war, icons continued to hang in public places. In addition, the social revolution that took place in Russia developed new subjects that began to appear in iconography, which is clearly demonstrated by the icon with the name “Physical Labor of the Holy Family” being a part of the collection of the Museum of the History of Religion in St. Petersburg. At that time, such or similar subjects in iconography were called “working on” icons. However, gradually the iconoclastic policy of the Bolsheviks became widespread and its apogee can be called the burning of icons, which can also be considered the apogee of the atheistic campaign.